FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 11 TAHUN 2001 TENTANG PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2018 - Ardi Syurya; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was motivated by the arrangement and guidance of Street Vendors in Simpang Baru Village, Tampan District, Pekanbaru City. Based on the Regional Regulation of Pekanbaru City Number 11 of 2001 concerning the Arrangement and Development of Street Vendors is one of the potential national development is the informal sector business, including the street vendors need to get guarantees including protection, guidance and regulation in making efforts to be efficient and effective and improve their welfare. This study directs how the evaluation of Regional Regulation No. 11 of 2001 concerning the Arrangement and Development of Street Vendors was carried out in Tampan Subdistrict, Pekanbaru City and the factors that influenced the Street Vendor Arrangement and Coaching conducted in Tampan District, Pekanbaru City. This research is a qualitative approach research, this research was conducted in Kuantan Singingi District, the technique used to collect data in this study was interviews and documentation. Based on the results of the previous research and discussion, several conclusions can be taken, namely the concept of coaching in Article 7 of Perda Number 11 of 2001 focused only on efforts to provide guidance and counseling. The pattern of guidance and counseling is not explained in detail, and does not move on how to create empowered street vendors and obtain legal protection. While the concept of supervision carried out by the Pekanbaru City Government does not also mention which agencies are authorized to supervise and how the supervision pattern will be carried out.Keywords: Policies and Street Vendors